UJI DAYA TERIMA DAN KANDUNGAN GIZI KERUPUK IKAN NILA (Oreochoromis Niloticus) DAN KOLANG KALING - Nur Syakirah; Zulhaida Lubis; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2018)
Crackers in general is a snack food that contains fat, the frying process is a contributor of fat content in crackers. Sugar palm fruit that has a high enough fiber can be used as an additional material for the making of crackers, besides nile tilapia can also be used as additional material for making crackers to add nutrient content in it. Crackers is one of the preferred snack people. This research purpose was to determine the acceptability test and nutritional content of crackers with the addition of nile tilapia and palm fruit. The type of research was an experiment conducted by completely randomized design. There were 2 treatment, the first treatment with composition nile tilapia 50%, sugar palm fruit 10%, tapioca flour 40%, and second with composition the nile tilapia 10%, palm fruit 50% and tapioca flour 40%. Test acceptability crackers done to 30 people the panel are student of public health faculty of University Sumatera Utara Medan, nutrient analysis was analyzed in the Laboratory of Industrial Research and Standarization Agency Medan. Data was analyzed by using Wilcoxon test . The results research showed that based on color and texture , the crackers that preferred is with the nile tilapia starch 10 %, sugar palm friut 50 % with total score 334 and nutrition content crackers is proteins 5,22 % ,fiber 0,98%, fat 25,4% . While based on smell and teste that was aqually favorable. Crackers it suggested can be consumed as a snack food or food variation for familly, school children, and teenagers. Can contribute to the protein that is enough from the needs of daily to prevent protein deficiency Keywords: Nile Tilapia, Sugar Palm Fruit, Crackers, Acceptability, Nutrient Content